Managing Obesity in Primary Care: Breaking Down the Barriers - Forgione, Nicholas (Adv Ther, 2018)
Several Australian obesity management guidelines have been developed for general practice but, to date, implementation of these guidelines has been shown to be inadequate. In this review, we explore the barriers to obesity treatment and propose a four-stage plan to manage individuals with obesity in general practice using a framework of a multidisciplinary team. Funding: Novo Nordisk.